Influence of fracture deformation on grout penetrability in fractured rock masses - Xiao, Fei (2022)
Fracture deformation during grouting is a hydro-mechanical coupled dynamic process. Some studies indicated that an increase in grouting pressure can accelerate the grouting process, while some other investigations concluded that a high grouting pressure would weaken the grouting effect for fine fractures due to fracture deformation. Though the assumption that an increase of grouting pressure to shorten grouting time has been used in engineering practices for a long time, there is a lack of sufficient supporting theories to verify the assumption. Moreover, there are no existing criteria to quantify the magnitude and degree of impact of fracture deformation on grout flow through fractures. The present paper therefore aims to quantitatively evaluate the dynamic process of fracture deformation and its impact on grout penetrability. Fracture deformation is a dynamic process as both the range of grout penetration and injection pressure are time dependent, so a theoretical pseudo-coupling model is proposed, including an analytical model to determine time varying grouting parameters of two neighboring fractures and a numerical model to assess the associated fracture deformation. Design of Experiment (DOE) and sensitivity analysis are utilized to determine the characteristics of fracture deformation and critical factors affecting its magnitude and distribution. It is found that the apertures, the aperture difference, and the stiffness of the two neighboring fractures are the three most important factors, and a large deformation occurs when both fractures are of small apertures. The ratio of fracture aperture to D95 of cement particle has a significant impact on grout penetrability, whereas the associated impact could be much lower by considering dynamic fracture stiffness.